Healthcare needs, experiences and treatment burden in primary care patients with multimorbidity: An evaluation of process of care from patients' perspectives - Xiu‐Jing Hu; Harry H. X. Wang; Yu‐Ting Li; Xiao‐Ya Wu; Yi Wang; Jia‐Heng Chen; Jia‐Ji Wang; Samuel Y. S. Wong; Stewart W. Mercer (Wiley, 2022)
Abstract Background Patients with multimorbidity often experience treatment burden as a result of fragmented, specialist‐driven healthcare. The 'family doctor team' is an emerging service model in China to address the increasing need for high‐quality routine primary care. Objective This study aimed to explore the extent to which treatment burden was associated with healthcare needs and patients' experiences. Methods Multisite surveys were conducted in primary care facilities in Guangdong province, southern China. Interviewer‐administered questionnaires were used to collect data from patients (N = 2160) who had ≥2 clinically diagnosed long‐term conditions (multimorbidity) and had ≥1 clinical encounter in the past 12 months since enrolment registration with the family doctor team. Patients' experiences and treatment burden were measured using a previously validated Chinese version of the Primary Care Assessment Tool (PCAT) and the Treatment Burden Questionnaire, respectively. Results The mean age of the patients was 61.4 years, and slightly over half were females. Patients who had a family doctor team as the primary source of care reported significantly higher PCAT scores (mean difference 7.2 points, p < .001) and lower treatment burden scores (mean difference −6.4 points, p < .001) when compared to those who often bypassed primary care. Greater healthcare needs were significantly correlated with increased treatment burden (β‐coefficient 1.965, p < .001), whilst better patients' experiences were associated with lower treatment burden (β‐coefficient −0.252, p < .001) after adjusting for confounders. Conclusion The inverse association between patients' experiences and treatment burden supports the importance of primary care in managing patients with multimorbidity. Patient Contribution Primary care service users were involved in the instrument development and data collection.